Poluição do Solo na Bacia Hidrográfica do Córrego Raizal em Araguaína (TO) - OLIVEIRA, Sara Emilly Nascimento (Universidade Federal do Tocantins, 2024)
This undergraduate thesis analyzed the soil pollution in the Raizal stream watershed in Araguaína, state of Tocantins. The methodology used in this work is based on bibliographic references about pollution, soils, watersheds and canalization. It also uses environmental characterization, satellite images, photographs and field work. From the analyses it was identified that most of the pollution comes from the actions of the community itself and others due to the little that is invested in basic sanitation. Furthermore, a good point is the vegetation that is still alive; however, the silting is persistent and the problems have evolved. With this, it is necessary to have a restoration project for the area. Investment in landscape maintenance, municipal supervision, or even leisure activities for the community without having to cut down the vegetation. In addition to an environmental education program for local residents that relies on the collaboration of the community for the preservation of the site, because even with all the proposed measures, the population needs to be aware not to damage the public patrimony. This academic work is necessary, since the environment is the vital means for human survival.